National scientific production in the special education area and daycare - de VITTA, Fabiana Cristina Frigieri [UNESP]; Sgavioli, Ana Júlia Ribeiro [UNESP]; Scarlassara, Bárbara Solana [UNESP]; Novaes, Carla Francielly Martini [UNESP]; Cruz, Girlene de Albuquerque [UNESP]; Moura, Mariana Martins [UNESP] (My University, 2018)
This paper aims to describe the scientific production in the Special Education area upon educational care offered to children aged from zero to three, initial stage of Early Childhood Education for the past 25 years. The database used as a search source were the Scientific Electronic Library Online (SciELO), Periódicos Eletrônicos em Psicologia (PEPSIC), Portal de Periódicos Capes/MEC; Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) and Red de Revistas Científicas da América Latina Y el Caribe, España y Portugal (REDALYC), and, as descriptors, the terms “educação especial” (special education), “educação inclusiva” (inclusive education),”inclusão” (inclusion) and “creche” (daycare facility), from 1993 to 2017. Twenty five papers, among them seventeen doctoral dissertations and master’s theses and eight papers. After a thorough reading of the objectives, methods and results, it was verified that the public policy themes of Early Childhood Education and Special Education; inclusive daycare facilities: case reports; education of professionals and conceptions about inclusion contemplate the discussions in the area. Inclusion in daycare is still incipient, both in official documents and in practice. However, the education of professionals for this reality strongly influences the perception and conceptions they have of children and activities in educational contexts. Therefore, new perspectives on these contexts are important, in order to produce materials that allow us to identify fragilities, successful experiences and relevant discussions that help to improve the quality of the services offered to that age group.
A produção científica nacional na área de educação especial e a creche
Keywords: Daycare; Inclusion; Inclusive education; Research results; Special education